Arts Education and Visual Communication in Character Design of the Nusa Five Serial Comic Character by Sweta Kartika - Aditia, Rafinita; Aditia, Bahrurrizqi (EDUCASIA: Jurnal Pendidikan, Pengajaran, dan Pembelajaran, 2024)
Comics have become one of the most influential media in popular culture in Indonesia. The comic Nusa Five by Sweta Kartika is a prominent example of this, incorporating elements of Indonesian culture into its character designs. This research aims to conduct an in-depth analysis of the design of the main characters in the comic Nusa Five to understand how arts education and visual communication play a role in creating characters that reflect the diversity of Indonesian culture. Character design analysis was carried out using a qualitative approach which involved observing the shapes, colors, textures and expressions of the characters in the comic Nusa Five. Data were analyzed to identify ways in which arts education and visual communication influence character formation. The results of the analysis show that art education provides a strong understanding of the use of visual elements to create unique and interesting characters. Meanwhile, visual communication strengthens visual narratives and conveys deep messages to readers. Even though there are some weaknesses in character design, arts education and visual communication remain an important foundation in creating strong and cohesive characters that reflect Indonesian culture. With a better understanding of the principles of visual art and design, Indonesian artists and designers can continue to produce work that respects and well represents the archipelago's cultural diversity.